Processos coletivos no teatro para crianças: dramaturgia, encenação e suas relações autorais - Andre Ferraz Sitonio de Assis (2017)
Study of the scenic and dramaturgical processes of three theater shows for children held in Belo Horizonte, Minas Gerais, Brazil, between 2007 and 2012: Circo do Lixo [Trash Circus] (2007), Pra Lá do Arco-Íris [Beyond Rainbow] (2011), and O Mistério da Bomba H______ [The Mystery of the 'Chicken' H-Bomb] (2012). To this end, we conducted a mutual comparison between these assemblies having one common focus of analysis the fact that in all of them, the writing (or rewriting) of dramaturgical text have been held collectively by the participants of the scenic creation process. The dramaturgy here is understood as plot made to underpin the staging, which also builds signs that help weave on the scene, this same plot. We investigate what procedures creation and/or recreation dramaturgical used in these shows and how this drama was coming to life through the scenic assembly process. For this, we conducted analysis of performances and interviews with the participants of assemblies, in which questions were raised about the scenic communication with children and the dramaturgical creation methodologies used.